Pemanfaatan Tumbuhan dalam Upacara Pernikahan Adat Lampung Pepadun Kabupaten Way Kanan - Winandari, Ovi Prasetya; Saputri, Dwijowati Asih; Oktaria, Oktaria (Universitas Bengkulu, 2025)
The cultural, linguistic, and ethnographic diversity of Indonesia is attributable to the country's numerous ethnic communities. One of the tribes in Indonesia, the Lampung Pepadun in Lampung Province, has a unique marriage ritual that is of interest for academic investigation. This study aims to identify the types of plants used in the traditional wedding ceremony of the Lampung Pepadun people in Negara Batin and Pakuan Ratu Districts, Way Kanan Regency, as well as to understand the benefits or symbolic meanings of these plants in the wedding rituals. This research employs a qualitative method with data collection techniques including observation, documentation, and interviews. The sampling techniques used are snowball sampling and purposive sampling. The findings reveal that 17 types of plants are used in the Lampung Pepadun traditional wedding ceremony, namely areca nut, Bryophyllum (cocor bebek), pandan water/rumbai, peanuts, cinnamon, henna leaves, banana, jasmine flowers, corkwood, coconut, betel leaves, rice, mini bamboo grass, sugarcane, gambier, coffee, and tobacco. Thus, it can be concluded that the Lampung Pepadun traditional wedding ceremony in Way Kanan Regency involves the use of 17 types of plants, each of which holds specific symbolic meanings and benefits in the ritual.